Power and energy [1999 technology analysis and forecast]. - Sweet, W.
This article presents a power and energy technology analysis and forecast for 1999. The subjects covered include photovoltaics, PV power systems, solar arrays, nuclear power and free market spot electricity pricing
Keywords: AD 1999.; PV power systems; Free electricity markets; Nuclear power; Photovoltaics; Solar arrays; Spot electricity pricing; Technology analysis; Technology forecast